Untreated depression and tuberculosis treatment outcomes, quality of life and disability, Ethiopia - Ambaw, Fentie (Bull World Health Organ, 2018)
OBJECTIVE: To investigate the association between comorbid depression and tuberculosis treatment outcomes, quality of life and disability in Ethiopia. METHODS: The study involved 648 consecutive adults treated for tuberculosis at 14 primary health-care facilities. All were assessed at treatment initiation (i.e. baseline) and after 2 and 6 months. We defined probable depression as a score of 10 or above on the nine-item Patient Health Questionnaire. Data on treatment default, failure and success and on death were obtained from tuberculosis registers. Quality of life was assessed using a visual analogue scale and we calculated disability scores using the World Health Organization’s Disability Assessment Scale. Using multivariate Poisson regression analysis, we estimated the association between probable depression at baseline and treatment outcomes and death. RESULTS: Untreated depression at baseline was independently associated with tuberculosis treatment default (adjusted risk ratio, aRR: 9.09; 95% confidence interval, CI: 6.72 to 12.30), death (aRR: 2.99; 95% CI: 1.54 to 5.78), greater disability (β: 0.83; 95% CI: 0.67 to 0.99) and poorer quality of life (β: −0.07; 95% CI: −0.07 to −0.06) at 6 months. Participants with probable depression had a lower mean quality-of-life score than those without (5.0 versus 6.0, respectively; P < 0.001) and a higher median disability score (22.0 versus 14.0, respectively; P < 0.001) at 6 months. CONCLUSION: Untreated depression in people with tuberculosis was associated with worse treatment outcomes, poorer quality of life and greater disability. Health workers should be given the support needed to provide depression care for people with tuberculosis.